Effect of intravenous dextran 70 and pneumatic leg compression on incidence of postoperative pulmonary embolism. Issue 6047 (27th November 1976) - Browse, N L; Clemenson, G; Bateman, N T; Gaunt, J I; Croft, D N
Abstract : The incidence of pulmonary embolism and deep vein thrombosis was measured in 50 matched pairs of patients undergoing common surgical procedures with preoperative and postoperative ventilation-perfusion lung scans and the fibrinogen uptake test. One patient in each pair was treated with intravenous dextran 70 and pneumatic leggings. The incidence of pulmonary embolism among the treated patients was significantly reduced from 24% to 8%, but the incidence of deep vein thrombosis was not significantly reduced (34% to 24%).